Corruption in Colombia: Cartagena refinery case (2016)
From National Development Plan (PDN) 2003 – 2006 ‘Towards a Community State’ investment projects aimed at boosting the exploration and exploitation mining and hydrocarbons ( Act 812, 2003) in which it was proposed to be promoted to move on the implementation of Master Development Program (PMD) Cartagena Refinery also known as Reficar, due to the lack of expertise, knowledge and planning have made this megaproject into one of the biggest embezzlements and detriments of the largest public resources the nation has had.